2008
DOI: 10.1038/ncb1734
|View full text |Cite
|
Sign up to set email alerts
|

β1 Integrin deletion from the basal compartment of the mammary epithelium affects stem cells

Abstract: The mammary gland epithelium comprises two major cell types: basal and luminal. Basal cells interact directly with the extracellular matrix (ECM) and express higher levels of the ECM receptors, integrins, than luminal cells. We show that deletion of beta1 integrin from basal cells abolishes the regenerative potential of the mammary epithelium and affects mammary gland development. The mutant epithelium was characterized by an abnormal ductal branching pattern and aberrant morphogenesis in pregnancy, although a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
237
1
2

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(255 citation statements)
references
References 27 publications
12
237
1
2
Order By: Relevance
“…Such cells have been suggested as the origin of ER-positive breast cancer (Dontu et al, 2003;Molyneux et al, 2007;Arendt et al, 2011), but until now it has not proven possible to prospectively isolate them. Importantly, cKit was required for progenitor function and is therefore only the second mammary stem/progenitor marker, after b1 integrin (Taddei et al, 2008), to be shown to have a functional role in the gland. Luminal Sca-1 À ER À c-Kit þ cells formed >50% of the epithelial content of the mammary gland, consistent with a report showing reciprocal staining of c-KIT and ER in the human breast (Westbury et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such cells have been suggested as the origin of ER-positive breast cancer (Dontu et al, 2003;Molyneux et al, 2007;Arendt et al, 2011), but until now it has not proven possible to prospectively isolate them. Importantly, cKit was required for progenitor function and is therefore only the second mammary stem/progenitor marker, after b1 integrin (Taddei et al, 2008), to be shown to have a functional role in the gland. Luminal Sca-1 À ER À c-Kit þ cells formed >50% of the epithelial content of the mammary gland, consistent with a report showing reciprocal staining of c-KIT and ER in the human breast (Westbury et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Terminally differentiated cells do not transplant or form colonies in vitro Stingl et al, 2006;AsselinLabat et al, 2007;Sleeman et al, 2007). Using flow cytometry and functional assays, stem cells have been localised to the basal cell layer, whereas progenitors are found in large numbers in the luminal population Stingl et al, 2006;AsselinLabat et al, 2007;Sleeman et al, 2007;Taddei et al, 2008). We have recently demonstrated that oestrogen receptor-alpha-negative (ER À ) luminal progenitors are the origin of BRCA1-associated breast cancers and likely of the majority of 'basal-like' breast cancers not linked to a family history (Molyneux et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A luciferase-based transgenic mouse model for MaSC activity did reveal luciferaseexpressing cells in both basal and myoepithelial locations [22]. Notably, when the MaSC marker CD29 is deleted from the basal compartment of the mammary gland, the mammary epithelial cells can no longer reconstitute a new mammary gland, but they can form alveoli late in pregnancy [18], suggesting a distinct MaSC population. Similar results were also obtained when the Wnt receptor LPR5 was deleted [23].…”
Section: Identification Of Mascsmentioning
confidence: 99%
“…Fragments of mammary epithelium or 1,000-5,000 sorted BCs in 10 ll of 50% growth-factor-reduced matrigel (BD Biosciences, San Diego, CA, http://www.bdbiosciences.com) were implanted into the inguinal fat pads of 3-week-old nude BALB/c females cleared of endogenous epithelium as described elsewhere [23]. In limiting dilution assays, 500-100,000 of total unsorted mammary cells per fat pad were transplanted in matrigel.…”
Section: Transplantation Assaysmentioning
confidence: 99%
“…The inguinal mammary glands of four to six 20-week-old virgin females were pooled to prepare single-cell suspensions, and cells were processed for flow cytometry as described [12,13,23]. The following conjugated antibodies were used: anti-CD24-PE (clone M1/69; BD Pharmingen, San Diego, CA, http:// www.bdbiosciences.com), anti-CD49f-FITC (clone GoH3; BD Pharmingen), anti-CD45-APC (clone 30-F11; Biolegend, San Diego, CA, http://www.biolegend.com), anti-CD31-APC (clone MEC13.3; Biolegend), and anti-Ly6A/E-PE-Cy5 (clone D7; eBiosciences, San Diego, CA, http://www.ebiosciences.com).…”
Section: Preparation Of Mammary Epithelial Cells and Cell Cycle Analysismentioning
confidence: 99%